STUDY OF BARLEY SOURCE MATERIAL IN THE ENVIRONMENTS OF ALTAI TERRITORY - G. M. Mousalitin; V. A. Boradoulina; Zh. V. Kouzikeev (Труды по прикладной ботанике, генетике и селекции)
In order to find new sources of agronomic traits, 402 barley accessions from different ecological and geographic zones were studied. Productivity, 1000 grain weight, grain weight per spike, number of fertile spikes per plant, resistance to covered smut, drought tolerance of accessions were evaluated. Promising breeding material was obtained. Key words: barley, collection, breeding, agronomic traits, accessions, productivity, disease resistance.